Chairil Anwar Service Literature Practices, 1942-1949 - Arif Setyawan (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Chairil Anwar's literary resistance practices in 1942-1949 were supported by ‘literary habitus’--foreign and local literature, literary totality, and literary rationality-- as a foundation with the support of ‘literary modal’ --literary totality, literary rationality, and ideals of literature-- with consideration of the ‘literary fields’.Although the dominance of a ‘pujangga baru’ generation through literary practices is quite strong, Chairil Anwar's ‘literary practice’ is a successful practice.This success was marked by several things, including (1) Chairil's poetry writing model was considered as a new model that was not available before in Indonesian literature; (2) the influence of Chairil's literary practice which is growing in Indonesian literary society; (3) Chairil's coronation as a pioneer of the 45th generation; and (4) the increasingly massive publishing of Chairil's works which certainly brings 'capital modal' to Chairil's family. Keywords: literary resistance practices, Chairil Anwar, 1942-1949 Abstrak Praktik sastra perlawan Chairil Anwar pada tahun 1942-1949 didukung oleh 'habitus sastra' --sastra asing dan lokal, totalitas sastra, dan rasionalitas sastra-- sebagai landasan dengan dukungan 'modal sastra' --totalitas sastra, rasionalitas sastra, rasionalitas sastra , dan cita-cita sastra-- dengan pertimbangan 'ranah sastra'. Meskipun dominasi generasi 'pujangga baru' melalui praktik sastra cukup kuat, 'praktik sastra' Chairil Anwar adalah praktik yang berhasil. Keberhasilan ini ditandai oleh beberapa hal, antara lain(1) Model penulisan sajak Chairil dianggap model baru yang belum ada sebelumnya di kesusasteraan Indonesia; (2) pengaruh praktik sastra Chairil yang semakin besar dalam masyarakat sastra Indonesia; (3) dinobatkannya Chairil sebagai pelopor angkatan 45; dan (4) semakin masifnya penerbitan karya-karya Chairil yang tentunya mendatangkan modal kapital bagi keluarga Chairil. Kata kunci: praktik sastra perlawanan, Chairil Anwar, Tahun 1942-1949